Bioactivity of Purple Sweet Potato (Ipomea batatas) as Anti Inflammatory Agent: Review - Shella Carlina Tasya; Paula Mariana Kustiawan (State University of Gorontalo, 2023)
This Inflammation is a defensive response to tissue damage that occurs locally. NSAID (Non Steroid Anti-Inflammatory Drugs) and AIS (Antiinflammatory Steroids) have been used in Indonesia to treat inflammation but have side effects on the body. Purple sweet potato leaf (Ipomoea batatas) is one of the herbal medicines used by the community to treat inflammation. This research is a literature review by collecting information from Google Scholar, PubMed, Scopus, and Garuda. The results showed that the active anti-inflammatory compounds in purple sweet potato leaves were flavonoids. Flavonoids can work as anti-inflammatory compounds by passing through several pathways such as inhibition of cyclooxygenase (COX) and lipoxygenase enzyme activities, inhibition of neutrophil degranulation, inhibition of histamine increase, and inhibition of leukocyte accumulation. Purple sweet potato (Ipomoea batatas) leaves are scientifically proven to have anti-inflammatory activity as evidenced by the presence of compounds that have anti-inflammatory effects and can be developed into products for inflammation.